Answer:
(2187 *y∧3) / (x∧10 *z) You must know a∧m * a∧n = a∧(m+n) and
a∧m / a∧n = a∧(m-n)
Step-by-step explanation:
First I will rewrite your expression
( 9*x∧(-2)*y∧(-3)*z∧4)∧2 / (3*x∧(-2)*y∧3*z∧(-3))∧(-3) =
= (9∧2) *( (x∧(-2))∧2) * (y∧(-3))∧2 * (z∧4)∧2 / (3∧(-3)) * (x∧(-2)∧(-3)) * ((y∧3)∧(-3)) * (z∧(-3)∧(-3)) =
= ((3∧2)∧2) * (x∧(-4)) * (y∧(-6)) * (z∧8) / (3∧(-3)) * (x∧6) * (y∧(-9)) *(z∧9) =
= (3∧4)/(3∧(-3)) * (x∧(-4-6)) * (y∧(-6-(-9))) * (z∧(8-9) =
= (3∧(4-(-3))) * (x∧(-10)) * (∧y(-6+9)) * (z∧(-1)) = (3∧(4+3) * (x∧(-10)) *(y∧3) * (z∧(-1)) =
(3∧7) * (x∧(-10)) * (y∧3) * (z∧(-1)) = (2187 * y∧3) / (x∧10 * z)
Good luck!!!